2021
DOI: 10.1177/00405175211039573
|View full text |Cite
|
Sign up to set email alerts
|

Accurate simulation of draped fabric sheets with nonlinear modeling

Abstract: This paper reports a numerical approach, based on a nonlinear particle spring model and a collision detection procedure, to simulate the shape of a draped cloth, or a flexible sheet, together with a simple but precise three-dimensional shape reconstruction method for real fabric applications. The latter is utilized to verify the accuracy of the proposed drape simulation model. The drapes of four types of fabric on a cylinder are simulated, and the results are compared with the reconstructed shapes of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…They reported that the fabric's physical parameters have a strong effect on the fabric drape form, such as the tensile, elongation, and stiffness. The material differential effect was observed under the same condition of simulation [11]. Miguel et al tested the fitting of two fabrics using a normal skirt to assess the fitting of a jacket, the fabrics are similar, but the first fabric is one layer and the second is a double layer [12].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…They reported that the fabric's physical parameters have a strong effect on the fabric drape form, such as the tensile, elongation, and stiffness. The material differential effect was observed under the same condition of simulation [11]. Miguel et al tested the fitting of two fabrics using a normal skirt to assess the fitting of a jacket, the fabrics are similar, but the first fabric is one layer and the second is a double layer [12].…”
Section: Introductionmentioning
confidence: 86%
“…al., demonstrated that the drape analyses are required because the drape coefficient test results (the reflection of drapped sample shadow, as Cusick drape meter standard method) are not sufficient to describe well the fabric drape behavior on the human body on garment simulation software [10]. Chen et al studied the difference between the drape of square and circular samples and make a comparison [11]. Also, they made several ways of capturing the sample draped, with three methods; the 1st one is capturing the normal photo, the 2nd is 3D scanning and the 3rd is reconstructing the sample drapped on a virtual cylinder object on 3D software.…”
Section: Introductionmentioning
confidence: 99%
“…3 different way of the draped samples are captured 2D photo, 3D scanning and reconstructed virtually on 3D software. It is reported that, the mechanical properties have a strong relationship with the drape coefficient, in both situation real and virtual 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Effects of draping: (a) photographs of real cloth items; (b) reconstructed three-dimensional images and (c) simulation results. Case 1: cotton fiber; Case 2: fibrilia; Case 3: polyester fiber; Case 4: 10% cotton and 90% polyester fiber 24.…”
mentioning
confidence: 99%
“…Thirdly, researchers have also launched studies on virtual fitting based on human posture, such as Han X et al 5 and Bowen et al., 22 which helped to optimize the effect of simulation following posture for real-time fitting. Finally, the collision problem has been studied by researchers early on, such as Ling et al., 23 Yong et al., 6 and Chen et al., 24 and a variety of theoretical approaches have been proposed to reduce the computational effort and solve the cloth penetration problem. The cloth modeling and simulation technology is made up of multiple links, of which these four perspectives have research coherence and are processed sequentially.…”
mentioning
confidence: 99%